Improvement of students’ scientific writing in a middle-years science classroom - Wood, Duncan Michael (Curtin University, 2015)
This thesis illustrates a mixed-methods action-research evaluating impact of selected intervention strategies on writing skills of Science students in a mixed ability year 6 class. Scaffolding, peer/self-assessment and metacognitive journaling were implemented as part of the students’ scheme of work over 3 months. Using interviews, work-samples and anecdotal records, it was established that the students improved their writing skills and self-efficacy towards writing in Science as a result of the use of these strategies.